Presentation Technology as a mediator of learners’ retention and comprehension in a History classroom (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The insistence that presentation technology should be incorporated into all areas of the curriculum applies to the teaching of History equally as to other subjects. Although technology has been placed in the hands of teachers, little training on how to adapt the technology to History has come with it. Three explanatory research questions were formulated for this study dealing with South African History teachers’ experiences of presentation technology as teaching and learning tool, and the format of more history-friendly PowerPoint slides to maximise History learners’ long-term retention and comprehension of the subject content. The purpose of this study was to put forward History teachers’ opinion on the role of presentation technology as a mediator of learning, and to use the outcomes of the empirical study to identify ways in which PowerPoint slides can be best designed and used to improve the learners’ long-term retention and comprehension. A qualitative intrinsic case study research design was used for the study. Individual one-toone interviews were conducted with two teachers. A deductive approach was used for the data analysis. The results of the data analysis revealed that both of the interviewees experienced the use of PowerPoint presentations as an improvement in their classes. However, both indicated that one of the greatest disadvantages of the use of PowerPoint slides was the lack of interactivity and discussions during the slide shows. Johnson’s (2011) history-friendly PowerPoint pedagogy (interactivity, nutshell narratives, meta-cognition and timelines and flow charts) was put forward to promote interactivity and discussion during PowerPoint slide shows.
Keywords: Constructivism; PowerPoint slides; Retention; Comprehension; History-friendly pedagogy; Nutshell narratives